Glucose sensing O‐GlcNAcylation pathway regulates the nuclear bile acid receptor farnesoid X receptor (FXR). Issue 5 (24th March 2014) - Berrabah, Wahiba; Aumercier, Pierrette; Gheeraert, Céline; Dehondt, Hélène; Bouchaert, Emmanuel; Alexandre, Jérémy; Ploton, Maheul; Mazuy, Claire; Caron, Sandrine; Tailleux, Anne; Eeckhoute, Jérôme; Lefebvre, Tony; et al.
<x xml:space="preserve">Abstract</x> Bile acid metabolism is intimately linked to the control of energy homeostasis and glucose and lipid metabolism. The nuclear receptor farnesoid X receptor (FXR) plays a major role in the enterohepatic cycling of bile acids, but the impact of nutrients on bile acid homeostasis is poorly characterized. Metabolically active hepatocytes cope with increases in intracellular glucose concentrations by directing glucose into storage (glycogen) or oxidation (glycolysis) pathways, as well as to the pentose phosphate shunt and the hexosamine biosynthetic pathway. Here we studied whether the glucose nonoxidative hexosamine biosynthetic pathway modulates FXR activity. Our results show that FXR interacts with and is O‐GlcNAcylated by O‐GlcNAc transferase in its N‐terminal AF1 domain. Increased FXR O‐GlcNAcylation enhances FXR gene expression and protein stability in a cell type‐specific manner. High glucose concentrations increased FXR O‐GlcNAcylation, hence its protein stability and transcriptional activity by inactivating corepressor complexes, which associate in a ligand‐dependent manner with FXR, and increased FXR binding to chromatin. Finally, in vivo fasting‐refeeding experiments show that FXR undergoes O‐GlcNAcylation in fed conditions associated with increased direct FXR target gene expression and decreased liver bile acid content. Conclusion: FXR activity is regulated by glucose fluxes in hepatocytes through a direct posttranslational modification catalyzed by the glucose‐sensing hexosamine biosynthetic pathway. (Hepatology 2014;59:2022–2033)